Efektivitas Live Streaming dalam Membangun Kesadaran dan Keyakinan Konsumen terhadap Penjualan Suatu Produk - Amyrul Eza, Early; Fitriyah, Zumrotul (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
The shift in consumer shopping behavior toward e-commerce poses challenges for MSMEs in optimizing digital marketing strategies. This community service aimed to examine the effectiveness of live streaming in building consumer awareness and conviction toward body care product sales at CV Avero Indonesia. The participatory observation method was employed using the 5A Model approach (Aware, Appeal, Ask, Act, Advocate) developed by Kotler, Kartajaya, and Setiawan. Data were collected through direct observation of live streaming activities on the Shopee platform, focusing on audience response, interaction patterns, and sales achievements. The findings revealed that live streaming effectively increased body care product sales, with a significant rise from 300 units at the beginning of the year to 900 units at year-end. Contributing factors included attractive titles, professional visuals, live product demonstrations, real-time host-consumer interaction, and exclusive offers during broadcasts. However, technical issues such as internet stability and audio-visual synchronization require attention. This community service provides practical contributions for MSMEs in optimizing live streaming-based digital marketing strategies to enhance consumer awareness and encourage purchasing decisions in the digital era.